TOP MANAGEMENT STRATEGY IN IMPROVING COMPETENCE SPIRITUAL AND SOCIAL STUDENTS THROUGH IMPLEMENTATION STUDENTS UBUDIYAH ACTIVITIES OF SMK SULTAN AGUNG 2 DIWEK - Sholihul Anshori (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
This ubudiyah activity is carried out according to levels class with guided by different priests and teachers on duty. As for the purpose of study this is to know the top strategies management increase spiritual competence and social participants educate through implementation of activities ubudiyah (case study at sultan vocational school great 2 scallops (Jombang). As well as describe supporting factors and inhibitorin implementation activity the The objectives of this research are: 1).  To describe the strategy top management in improving spiritual competence 2). For describes top managements strategy in improving social competence  3) To describe top management strategiesin improving students spiritual and social competence through implementation worship activities at Sultan Agung 2 Diwek Vocational School Jombang. Ubudiyah activities have long been carried out at vocational schools Sultan Agung 2 Diwek, can really improve competence Spiritual students and students' social competence. Top management strategy in improving competence? spiritual and student social through the implementation of ubudiyah activities in Sultan Vocational School Agung 2 Diwek is by performing the Dhuha prayer cong regation, congregational Dhuhur prayer, religious lectures, PHBI activities, activities the ubudiyah others, for example, distribution of sacrificial meat, reading ask for forgiveness, distribution of basic necessities and others